2000
DOI: 10.1101/gr.148600
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Resolution Physical Mapping of Genomic Diversity in Candida albicans

Abstract: It has been suggested that Candida albicans, a diploid asexual fungus, achieves genetic diversity by genomic rearrangement. This important human pathogen may provide a system in which to analyze alternate routes to genomic diversity. C. albicans has a highly variable karyotype; its chromosomes contain a middle repeated DNA sequence called the Major Repeat Sequence (MRS), composed of subrepeats HOK, RPS, and RB2. RPS is tandemly repeated while the other subrepeats occur once in each MRS. Chromosome 7, the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 54 publications
3
75
0
1
Order By: Relevance
“…In most strains where chromosome translocations have been mapped, the translocation point is at an MRS (Chu et al, 1993;Navarro-Garcia et al, 1995;Iwaguchi et al, 2000Iwaguchi et al, , 2001. Chibana et al (2000) showed that several reciprocal translocations involving chromosome 7 occurred at the MRS locus. Thus, the MRS is likely to be directly involved in the process of chromosome translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most strains where chromosome translocations have been mapped, the translocation point is at an MRS (Chu et al, 1993;Navarro-Garcia et al, 1995;Iwaguchi et al, 2000Iwaguchi et al, , 2001. Chibana et al (2000) showed that several reciprocal translocations involving chromosome 7 occurred at the MRS locus. Thus, the MRS is likely to be directly involved in the process of chromosome translocation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of chromosome translocation involving chromosome 7 (Chu et al, 1993;Iwaguchi et al, 2000;Navarro-Garcia et al, 1995;Iwaguchi et al, 2001;Chibana et al, 2000). Both ends of the SfiI fragment 7F have been shown to be active sites for recombination, and each is flanked by major repeat sequences (MRSs).…”
Section: Introductionmentioning
confidence: 99%
“…Although large blocks of DNA, corresponding in several cases to the SfiI restriction fragments in C. albicans, are similarly organized in the two species, they are much less frequently arranged as pairs of chromosome homologues in C. dubliniensis. As in C. albicans, the MRS in C. dubliniensis seems to be a major site for chromosome reorganization (Chibana, Beckerman et al 2000) (Magee and Chibana 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The origin and function of the MRS are not known, but it is found only in C. dubliniensis and C. albicans. It is the site of most of the translocations which have been mapped in C. albicans, and it is responsible for much of the chromosome length polymorphism which exists in that organism (Chibana, Beckerman et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The hybridization data [41] provided evidence that translocation and reciprocal translocation might contribute to chromosomal polymorphism in P. brasiliensis and that chromosomal rearrangements could provide a means for genetic variation in this organism, as proposed to occur in Candida albicans, and other fungi and eukaryotes [43][44][45]. The results on the molecular karyotypes of pathogenic fungi demonstrate the overwhelmingly fluidity of chromosome organization among eukaryotes with small genomes, which probably contributes to the maintenance of genome functionality and control of gene expression.…”
Section: Chromosomal Polymorphism and Ploidymentioning
confidence: 84%